Palm Cooking Oil Refraction Index Measurement Using Single Slit Fraunhofer Diffraction Method - Supriyadi Supriyadi; Misto Misto; Yulia Hartanti (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2014)
Palm cooking oil refraction index measurement has been done in several temperature using single slit Fraunhofer diffraction method. Ratio between diffraction patterns at the air dan solution medium can be used to determine its refraction index. Using aquades as sample, was obtained refractive index 1.331 with the discrepancy 0.038%. Based on the refractive indexs measured for each temperature were obtained linear equation model: Y=-(0,00145±0,00021)X+(1,54232±0,01757)where R = -0,97266 and R^2=0,94606. Temperature changes influence strongly to refractive index changes of palm cooking oil sample, changes both inversely. Gradient of 0.00145 indicate that refractive index of palm cooking oil sample decrease slowly, so the quality is still good. Keywords : Palm Coocing oil, refractive index, temperature, Fraunhofer diffraction method